Cognitive reserve: a multidimensional protective factor in Parkinson's disease related cognitive impairment. Issue 4 (4th July 2022) - Ciccarelli, Nicoletta; Colombo, Barbara; Pepe, Fulvio; Magni, Eugenio; Antonietti, Alessandro; Silveri, Maria Caterina
ABSTRACT: We explored the association between cognitive reserve (CR) and Parkinson' s disease (PD) related cognitive deterioration. Forty PD patients and 12 matched healthy controls (HC) were enrolled. The PD group was balanced for the presence/absence of cognitive impairment. All participants underwent MOCA. CR was measured by the Brief Intelligence Test, and a new comprehensive tool, named Cognitive Reserve Test (CoRe-T), including sections on leisure activities and creativity. Participants with higher CR obtained a better MOCA score irrespective of the group they belonged to. At the same time, irrespective of the CR level, the performance of the HC group was always better in comparison to the PD group. Within the PD group, a higher frequency of leisure activities was associated to be cognitively unimpaired, independently by the severity of motor symptoms and age. CR could help to cope with PD-related cognitive decline. Its multidimensional nature could have important applications in prevention and rehabilitation interventions.